Answer:
6 - 4a
Explanation:
From the question given,
f(x) = 2 - x
2f(a) + f(2a) =.?
First, we shall obtain f(a). This can be obtained as follow:
f(x) = 2 - x
x = a
f(a) = 2 - a
Next, we shall obtain 2f(a). This is can be obtained as follow:
f(a) = 2 - a
2f(a) = 2(2 - a)
2f(a) = 4 - 2a
Next, we shall obtain f(2a). This can be obtained as follow:
f(x) = 2 - x
x = 2a
f(2a) = 2 - 2a
Finally, we shall determine 2f(a) + f(2a) as follow:
2f(a) = 4 - 2a
f(2a) = 2 - 2a
2f(a) + f(2a) =?
2f(a) + f(2a) = (4 - 2a) + (2 - 2a)
2f(a) + f(2a) = 4 - 2a + 2 - 2a
2f(a) + f(2a) = 4 + 2 - 2a - 2a
2f(a) + f(2a) = 6 - 4a
Therefore, 2f(a) + f(2a) is equivalent to 6 - 4a